THE INFLUENCE OF UTILITARIAN AND HEDONIC VALUES ON REPURCHASE INTENTIONS FOR COUNTERFEIT PRODUCTS TOWARD CUSTOMER SATISFACTION - Dhelviana Sukma Mawarni; Heriyadi Heriyadi; Erna Listiana; Juniwati Juniwati; Endah Mayasari (Jurnal Ekonomi, 2023)
This study aims to describe the factors that influence the purchase of counterfeit products which are mediated by customer satisfaction. There are 2 (two) variables, namely utilitarian shopping value and hedonic shopping value. Utilitarian shopping value relates to the purchase of an item because of its functional value, while hedonic shopping value involves the emotional experience of the shopping process itself. This study will examine how much influence utilitarian shopping value and hedonic shopping value have on repurchase intention in counterfeit products, especially in counterfeit shoes for the Adidas brand, which is mediated by customer satisfaction. Using Structural Equation Modeling (SEM) and AMOS statistical tools, this study examines the relationship between independent variables and dependent variables to support the hypotheses developed. Methods of data collection using a questionnaire with a number of respondents of 200 people. The results of this study indicate that utilitarian shopping value has a significant effect on customer satisfaction. Hedonic shopping value has a significant effect on customer satisfaction. Utilitarian shopping value has no significant effect on repurchase intention of counterfeit products. Hedonic shopping value has a significant effect on repurchase intention of counterfeit products. Customer satisfaction has a significant effect on repurchase intention of counterfeit products. Customer satisfaction has a mediating effect of utilitarian shopping value on repurchase intention in counterfeit products. Customer satisfaction has a mediating effect of hedonic shopping value on repurchase intention of counterfeit products.